HIV-1 Tat: Role in Bystander Toxicity - Ajasin, David; Eugenin, Eliseo A. (Frontiers in Cellular and Infection Microbiology, 2020)
HIV Tat protein is a critical protein that plays multiple roles in HIV pathogenesis. While its role as the transactivator of HIV transcription is well-established, other non-viral replication-associated functions have been described in several HIV-comorbidities even in the current antiretroviral therapy (ART) era. HIV Tat protein is produced and released into the extracellular space from cells with active HIV replication or from latently HIV-infected cells into neighboring uninfected cells even in the absence of active HIV replication and viral production due to effective ART. Neighboring uninfected and HIV-infected cells can take up the released Tat resulting in the upregulation of inflammatory genes and activation of pathways that leads to cytotoxicity observed in several comorbidities such as HIV associated neurocognitive disorder (HAND), HIV associated cardiovascular impairment, and accelerated aging. Thus, understanding how Tat modulates host and viral response is important in designing novel therapeutic approaches to target the chronic inflammatory effects of soluble viral proteins in HIV infection.